Polish and Bulgarian Somatic Phrases Justified with the Names of the Parts of the Body Designed for Thinking - Michow, Elżbieta (Respectus Philologicus, 2014)
The article includes the analysis of Polish and Bulgarian somatic phrases with the meaning justified with substantial components – the names of the parts of the body having a semantic feature ‘designed for thinking’ in the semantic structure. This semantic feature belongs to mental functions in the categories of semantic features and it justified the meaning of the number of collected phrases in Bulgarian (about 60) twice as big as in Polish (about 30). The most productive components of analysed phrases are NA (nomen anatomicum) Polish głowa (łeb), Bulgarian глава and мозък. NA Polish mózg and exceptionally NA Polish ciemię i mózgownica are rarely used in the function of the component. Furthermore, the observations of productivity of NA lead to the conclusion that metonymic alternations of NA: глава – мозък are used in Bulgarian more often. They are based on the same function of both exchanged parts of the body: designed for thinking. However, in Polish exceptional and rare metonymies are possible: głowa – ciemię and głowa – mózgownica. The semantics of Polish and Bulgarian phrases concerns two categories: 1) the process of thinking (as a way of learning and memorizing as well as upsetting oneself); 2) the characteristics and the evaluation of human’s intellectual abilities. A detailed analysis was conducted within the confines of collections that realize the relations of initial phase, continuation and finalization. Furthermore, it was proved that very productive metaphors that organize the imagery in Polish and Bulgarian somatic phrases are the ontological metaphor of a container and the structural metaphor of a machine.